2013
DOI: 10.1590/s2317-17822013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do respirador oral: uso do espelho de Glatzel e do peak nasal inspiratory flow

Abstract: OBJETIVO: Comparar o uso do espelho de Glatzel e do peak nasal inspiratory flow na avaliação de indivíduos respiradores orais, bem como analisar a correlação dos dois instrumentos. MÉTODOS: Foram avaliadas 64 crianças, sendo 32 respiradoras orais e 32 respiradoras nasais, na faixa etária de 4 a 12 anos. Os respiradores orais, diagnosticados de acordo com equipe multiprofissional, foram subdivididos de acordo com a causa da obstrução. Foram utilizados o espelho de Glatzel e o peak nasal inspiratory flow nos doi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
(37 reference statements)
0
4
0
2
Order By: Relevance
“…These outcomes mean that the smaller the nasal patency, the greater the perception of problems related to obstruction. Melo et al 25 have evaluated nasal and mouth-breathing children by Glatzel Mirror and PNIF. They concluded that the Glatzel Mirror could differentiate children with and without nasal obstruction, regardless of its cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outcomes mean that the smaller the nasal patency, the greater the perception of problems related to obstruction. Melo et al 25 have evaluated nasal and mouth-breathing children by Glatzel Mirror and PNIF. They concluded that the Glatzel Mirror could differentiate children with and without nasal obstruction, regardless of its cause.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that the use of this instrument in children may have some limitations, as they need their parents help to answer it and because their perception of obstruction symptoms is not very clear. Authors have suggested, for nasal obstruction evaluation, a combination of subjective and objective methods, complementing one another 16,25 . The hypothesis that children with nasal obstruction present craniocervical posture alteration was partially confirmed, since a greater head extension and the correlation between craniocervical measures and nasal patency were verified.…”
Section: Discussionmentioning
confidence: 99%
“…Within the area there is still no objective "gold standard" technique to evaluate the breathing mode, many times done in a subjective way and depending on the report of the signs and symptoms by the patient/caregiver (4) . A reliable, cost-effective, and non-invasive objective measure of nasal air ow still remains unknown (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Tendo em vista a utilização do Protocolo MBGR na prática clínica e em trabalhos científicos (BRITO, 2010;JOHANNS et al, 2011;MODOLO, 2012;Introdução ANDRADA E SILVA et al, 2012;PAVANI-SOVINSKI, 2012;PIZOLATO, FREITAS-FERNANDES, GAVIÃO, 2013;JANOCA et al, 2013;ROSAL, CORDEIRO, QUEIROGA, 2013;GIACCHINI, TONIAL, MOTA, 2013;MELO et al, 2013) e a importância da validação de instrumentos de avaliação, buscou-se validar o Protocolo MBGR para contribuir na compreensão das alterações relacionadas às funções de respiração, mastigação, deglutição e fala em pacientes adultos com DTM, uma vez que estes apresentam distúrbios miofuncionais orofaciais.…”
Section: Lista De Ilustraçõesunclassified